Reverse Tissue Expansion in Gastroschisis: What to do if the Defect is too large to close after Silo Removal? - Adikibi, Boma T; O'Toole, Stuart (Journal of Neonatal Surgery, 2014)
A female baby with an antenatal diagnosis of gastroschisis was transferred to our institution. The defect was large but the bowel was in good condition and a silo was placed. After successful reduction of the bowel the abdominal wall defect was too large to allow fascial or even skin closure. We utilised a Gore-tex patch with two prolene purse string sutures placed concentrically to enable the diameter of the patch to be sequentially reduced. This enabled gradual stretching of the tissues with a progressive reduction in the size of the defect. The patch was removed after 8 days and a delayed fascial closure was achieved.